PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUDIOVISUAL BERBASIS APLIKASI CANVA TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS III SEKOLAH DASAR - Desnika, Fathiya; Muhammadi; Sukma, Elfia; Safitri, Serly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using audiovisual learning media based on the Canva application on students’ learning interest in Indonesian language learning in grade III elementary school. The background of this research is the low level of students’ learning interest caused by the limited use of innovative learning media, resulting in less active participation and low enthusiasm during the learning process. This research employed a quantitative approach with a quasi-experimental method using the Nonequivalent Control Group Design. The research subjects consisted of third-grade students at SD Negeri 20 Piai as the experimental class and SD Negeri 33 Tanjung Sabar as the control class. Data were collected using a learning interest questionnaire that was administered before and after the treatment. The data were analyzed using prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing using an independent samples t-test with the assistance of IBM SPSS Statistics 27. The results showed that the significance value of the independent samples t-test was 0.001 < 0.05. Therefore, H₀ was rejected and H₁ was accepted, indicating that the use of audiovisual learning media based on the Canva application had a significant effect on students’ learning interest in Indonesian language learning. These findings indicate that Canva-based audiovisual media can be an effective alternative learning medium to create more interesting, interactive, and student-centered learning.